Interferon alpha 2b or Mitomycin-C as Adjuvant Therapy of Pigmented Conjunctival Malignancy : A Literature Review: Oral Presentation - Observational Study - Resident - dr. meuthia rana amira primaputri (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To compare the efficacy and safety between Mitomycin C (MMC) and Interferon alpha-2b (IFN-α2b) eye drops as adjuvant therapy for conjunctival melanoma. Methods : Literature searching was conducted using PubMed, ScienceDirect, and Google Scholar. All studies that met the inclusion and exclusion criteria were categorized based on the level of evidence. The data of patients demographics, staging of disease, type of treatments, and outcomes of this review including local control rate, side effect, and recurrence and/or metastases were also reported. Results : From twelve articles, topical adjuvant chemotherapy with MMC and IFN α-2b showed favourable complete remission rate. Local control (complete remission) of IFN α-2b group is 46%, while in MMC group is 57%. The most side effect of MMC group were severe corneal-conjunctival irritation and corneal defect, while the IFN α-2b group showed mild side effect. Recurrency rate of IFN α-2b group and MMC group both is 35%. Metastases case of IFN α-2b group is 3.8%, while none of cases from MMC group metastases. Conclusion : Topical adjuvant chemotherapy with MMC and IFN α-2b showed favourable local control rate even though the recurrency rate also relatively high. Both medications showed promising results to reduce residual tumor size after wide excision surgery, preserving eye so reduce the chance of exenteration in various stages. It is important to consider adjuvant therapy following wide excision surgery as the first line treatment.